Ideal cycles of communication (or cognitions) in triads, dyads, and individuals - Tschan, Franziska (My University, 2002)
The relationship between the quality of communication cycles and performance was tested for triad and dyads, and the relationship between thought cycles and performance was tested for individuals. High-quality cycles conform to an ideal structure. This means that they start with action preparatory functions (orientation or planning) and end with the evaluation of a behavior performed. It was hypothesized that quality of cycles predicts performance above and beyond other process variables. For triads, a significant amount of additional variance in performance was explained by cycle quality after accounting for the effect of number of cycles communicated and cycle length (Study 1). The main findings are replicated for dyads (Study 2). In Study 3, individual actors performing the same task were asked to think aloud, and the protocols were analyzed in the same manner as group communication. Again, quality of thought cycles was related to higher performance,indicating similar functions of thinking for individual action and of communication for groups.
Keywords: SYSTEM